A new species of the family Sturmiidae (Collembola: Symphypleona) from Panama - Castaño-Meneses, Gabriela; Palacios-Vargas, José G. (Zootaxa, 2011)
Sturmius panamaensis sp. nov. from the canopies of the San Lorenzo Forest in Panama is described and illustrated. The new species lacks a pseudonychium on the ungues, has a smaller mucro than the other species in the genus, and females have long anal appendices. A key to identify the three species known in the family is provided.